2020
DOI: 10.1101/2020.05.06.077883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus activates a stem cell-mediated defense mechanism that reactivates dormant tuberculosis: implications in COVID-19 pandemic

Abstract: We postulate that similar to bacteria, adult stem cells may also exhibit altruistic defense mechanism to protect their niche. Here, we provide preliminary data on the altruistic stem cell (ASC) based defense against a mouse corona virus; MHV-1 infection. In a mouse model of mesenchymal stem cell (MSC) mediated M. tuberculosis (Mtb) dormancy, MHV-1 infection in the lung exhibited 20 fold lower viral loads than the healthy control mice, suggesting the potential enhancement of an anti-MHV-1 defense by Mtb. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 55 publications
1
50
0
5
Order By: Relevance
“…These findings raise human bone marrow derived stem cells as the site of Mtb latency ( 27 ). Recently, we have shown that stem cell altruism may be involved in Mtb -reactivation ( 28 ), and in the aerosol-induced immunity ( 29 ). These recent studies indicate the emerging role of BM stem cell niche in the pathogenesis and community transmission of Mtb .…”
Section: Introductionmentioning
confidence: 99%
“…These findings raise human bone marrow derived stem cells as the site of Mtb latency ( 27 ). Recently, we have shown that stem cell altruism may be involved in Mtb -reactivation ( 28 ), and in the aerosol-induced immunity ( 29 ). These recent studies indicate the emerging role of BM stem cell niche in the pathogenesis and community transmission of Mtb .…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that corona virus may activate a stem cell mediated defense mechanism, that accentuates activation of dormant TB. 5 Use of immune-modulators in moderate and severe COVID-19, as steroids and tocilizumab, may also lead to reactivation of latent TB in high TB burden country like ours. Concomitant use of anti-TB chemotherapy may also lead to drug-drug interaction and additive hepatotoxicity, if remdesivir has been used for treatment of COVID-19.…”
Section: Casementioning
confidence: 84%
“…As most TB in young children is acquired in their own household, social distancing measures that keep a family together for long periods of time are likely to result in more exposure of children to infectious TB index cases. Contact screening for COVID-19 should therefore include questions about TB in the household in order to protect young children from additional risks [11].…”
Section: Is Tuberculosis Treatment Different In People Who Have Both mentioning
confidence: 99%